2017
DOI: 10.3892/or.2017.5376
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-194 represses glioma cell epithelial-to-mesenchymal transition by targeting Bmi1

Abstract: MicroRNA-194 (miR-194) is frequently dysregulated in many types of cancer. However, the function of miR-194 in glioma remains unknown. In the present study, we aimed to investigate the biological functions of miR-194 in glioma and the potential molecular mechanism of miR-194 involved in glioma progression. We found that miR-194 expression was significantly reduced in glioma specimens and cell lines, as detected by real-time quantitative polymerase chain reaction (RT-qPCR) analysis. The overexpression of miR-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…**P < .01, ***P < .001, compared with the NC group Glioma is the most common and invasive type of major brain tumour, with a high yearly mortality rate worldwide. 19,20 It has now been clearly established that miRNAs have an important role to regulate the tumorigenesis and metastasis of glioma. 21,22 MiR-1275 is an intergenic miRNA, which is encoded by chromosome 6 and associated with tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…**P < .01, ***P < .001, compared with the NC group Glioma is the most common and invasive type of major brain tumour, with a high yearly mortality rate worldwide. 19,20 It has now been clearly established that miRNAs have an important role to regulate the tumorigenesis and metastasis of glioma. 21,22 MiR-1275 is an intergenic miRNA, which is encoded by chromosome 6 and associated with tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that GDNF can promote glioma cell growth by activating MAPK signaling [11, 50, 60], which is consistent with our findings. We found that hsa-miR-152-3p, hsa-miR-194-5p, hsa-miR-629-5p, and hsa-miR-3609b all are able to target MAPK, and hsa-miR-152-3p and hsa-miR-194-5p are both concerned with glioma development [61, 62]. In addition, MAP2K, MAP3K, and ATF2, the key factors in the MAPK signaling pathway, are also target genes of hsa-miR-629-5p, hsa-miR-3609, and hsa-miR-183-5p.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 MiR-194-5p has been found to be low expressed in glioma tissue and overexpression of miR-194-5p suppresses invasion and epithelial-mesenchymal transition of glioma cells. 44 Under serumdeprived condition, miR-194-5p was involved in the regulation of endothelial gene expression as well as the functional angiogenic activity. 21 In GECs, we found that miR-194-5p was low expressed.…”
Section: Combined Treatment Of Circ-usp1 and Mir-194-5p Promoted Domentioning
confidence: 99%